2018
DOI: 10.1136/thoraxjnl-2017-211453
|View full text |Cite
|
Sign up to set email alerts
|

Role of habit in treatment adherence among adults with cystic fibrosis

Abstract: Telephone: 0114 222 4386Word count: 1,099 words 2 ABSTRACT Among adults with CF, medication adherence is low and reasons for low adherence are poorly understood. Our previous exploratory study showed that stronger 'habit' (i.e. automatically experiencing an urge to use a nebuliser) was associated with higher nebuliser adherence. We performed a secondary analysis of pilot trial data (n=61) to replicate the earlier study and determine whether habit-adherence association exists in other cohorts of adults with CF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…The highest adherers commonly reported that they did their treatments automatically, indicating that it was habitual. This is consistent with recent research showing the importance of automatic motivation habits in adherence (Hoo et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ), including evidence that adherence interventions that focus on habit formation are the most effective (Conn & Ruppar, ). Habits mean that adherence requires less cognitive effort (Gardner, de Bruijn, & Lally, ), and this means that habits can be maintained in circumstances that might make treatment taking more challenging (Gardner, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest adherers commonly reported that they did their treatments automatically, indicating that it was habitual. This is consistent with recent research showing the importance of automatic motivation habits in adherence (Hoo et al ., ; Phillips, Cohen, Burns, Abrams, & Renninger, ), including evidence that adherence interventions that focus on habit formation are the most effective (Conn & Ruppar, ). Habits mean that adherence requires less cognitive effort (Gardner, de Bruijn, & Lally, ), and this means that habits can be maintained in circumstances that might make treatment taking more challenging (Gardner, ).…”
Section: Discussionmentioning
confidence: 99%
“…A range of qualitative studies, which have mainly used a thematic approach to analysis, and reviews have attempted to understand the factors influencing adherence to treatment in CF for adolescents and adults (Abbott, Havermans, & Hart, ; Arias‐llorente, García, & Martín, ; Foster et al ., ; George et al ., ; Hogan, Bonney, Brien, Karamy, & Aslani, ; Hoo, Boote, Wildman, Campbell, & Gardner, ; Horky, Sherman, Laura, Polvinen, & Rich, ; Lask, ; Macdonald et al ., ; Pakhale et al ., ; Sawicki, Heller, Demars, & Robinson, ). These have tended to find that adherence to treatment is reported to be influenced by the extent of treatment burden, having the time to do treatment, having a routine, forgetting to do treatment, a person's identity, perceptions of control, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…Routine has been shown to be advantageous in adherence in CF. Hoo et al 15 found that patients with higher levels of adherence had the highest habit scores, lower median intravenous antibiotic days and a trend towards higher forced expiratory volume in one second compared with those with low adherence. Habit formation is advantageous as it reduces the need for conscious effort.…”
Section: Discussionmentioning
confidence: 99%
“…Theories of behavioural maintenance 18 predict that supporting people to create habits for treatment, that is, taking treatments in response to specific contextual cues, can help to sustain adherence and to lower perceived treatment burden. 19 We developed a multi-component (complex) self-management intervention to support sustained treatment adherence, 20 incorporating objective adherence measurement, underpinned by behavioural science theory and designed to address gaps in CF care, with extensive input from people with CF. Since exacerbations are disruptive to patient life, they are an important patientcentred outcome and are commonly considered to indicate lung health.…”
Section: Why Read On?mentioning
confidence: 99%